Observatory on Critical Editions (Prassi Ecdotiche della Modernità Letteraria, 2017)
The project “An Observatory on critical editions” is promoted by the Department of Literature, Philolgy and Linguistics of Università degli Studi di Milano. The research group is formed by Alberto Cadioli, Paolo Chiesa, Stefano Martinelli Tempesta, William Spaggiari, Roberto Tagliani. By now, the research team also involves Paolo Borsa, Virna Brigatti, Massimiliano Gaggero, Rossana Guglielmetti, Giulia Ravera. Tha project was presented during the seminar held in Milan on September the 13th 2017 (please see the resume published in this issue of «Prassi Ecdotiche della Modernità Letteraria»: https://riviste.unimi.it/index.php/PEML/article/view/9272).
Keywords: Critical editions; Observatory